Isnyer Reformations-Drucke : Verzeichnis der in der Bibliothek der ev. Nikolauskirche in Isny vorhandenen Drucke aus den Jahren 1518 bis 1529 - Leuze, Otto (European History and Culture - Book Archive pre-2000., 1965)
Careful descriptions of 340 Reformation imprints 1518-1529, in alphabetical arrangement, with a useful introduction.